Recurrence Rate and Risk Factors for the Recurrence of Ovarian Endometriosis after Laparoscopic Ovarian Cystectomy. (27th January 2021) - Wacharachawana, Sornsittipong; Phaliwong, Paweena; Prommas, Sinart; Smanchat, Buppa; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun
Abstract : The aim of this study was to identify the recurrence rate and risk factors for the recurrence of ovarian endometriosis (OE) after laparoscopic cystectomy. This was a retrospective cross-sectional study. Subjects were OE cases who underwent laparoscopic ovarian cystectomy at Bhumibol Adulyadej Hospital (BAH). The period of this study was from January 2008 to December 2017. Ovarian histopathology and at least one-year follow-up after surgery were the prerequisite requirements. A total of 106 OE cases were included in the study. Subjects were classified into recurrence and nonrecurrence groups. It comprised of 24 and 82 cases, respectively. The mean age of the participant was 32.4 years old. The demographic characters of both groups were comparable. The recurrence rate after laparoscopic OE surgery in the present study was 22.6% (24/106). The average largest diameter of OE in the present study was 54.5 mm. Postoperative medical treatment (OR 3.15, 95% CI 1.14-8.74, p = 0.02 ) and postoperative pregnancy (OR 2.86, 95% CI 1.03-7.93, p = 0.04 ) were associated factors for recurrence decrement. The recurrence rate of OE after laparoscopic cystectomy was 22.6%. Postoperative medical treatment and postoperative pregnancy were a significant factor that lowered OE recurrence.